PERBEDAAN INSIDENSI DIABETES MELITUS TIPE 2 DAN HBA1C PADA POPULASI TERPAPAR-TIDAK TERPAPAR EMISI PABRIK SEMEN PADANG - Prima Adelin; Rismawati Yaswir; Zelly Dia Rofinda; Rizanda Machmud; Husna Yetti (Health and Medical Journal, 2021)
Background: Cement factory emission disrupt blood glucose control through insulin resistance mechanism, thus increasing incidence of type 2 diabetes mellitus (DM type 2). Aim: Aim of this study is to determine incidence’s differences of DM type 2 and mean HbA1c patients with DM type 2 within population exposed and unexposed cement Padang factory emission. Method: This was a cross sectional analytic study with cluster sampling that conducted on June-December 2015 with 129 and 125 participant from exposed and unexposed areas. Age of participants are 20-79 years old. Incidence is total new cases per total sample in exposed or unexposed area. HbA1c were measured with immunoturbidimetry method. Data were analyzed by chi-squared test to asses differences of two proportions and t test to asses differences of two averages. Results: The incidence DM type 2 are 3,9% and 7,2% respectively in exposed and unexposed areas, without significant difference (p>0,05). The mean HbA1c patients DM type 2 are 10,0(2,4)% and 8,8(1,6)% in exposed and unexposed areas, without significant difference (p>0,05). Conclusions: There were no significant differences incidence of DM type 2 and  mean HbA1c patients DM type 2 in the populations exposed and unexposed cement Padang factory emission. Cohort studies is required to see the effects of cement factory emission